Microbiological Quality Assessment of Ready-To-Eat Snacks Sold in Selected Primary Schools in Ovia North-East Local Government Area of Edo State, Nigeria - Omokhele, Henrietta Obueh; Ndukwe, Maduka; Aletile, Margret Eniola (FUDMA Journal of Sciences, 2026)
Ready-To-Eat (RTE) snacks prepared under unsanitary conditions and sold by unlicensed vendors at improper holding temperatures, without appropriate packaging, poses a health risk to consumers. This study is aimed at evaluating the microbiological quality of RTE snacks sold within the premises of three (3) selected primary schools coded ‘ADPS’, ‘OPS’, and ‘IPS’ in Ovia North-East LGA of Edo State, Nigeria. A total of thirty-nine (39) samples that comprise of 10 buns, 10 doughnuts, 10 sausage roll, and 9 meat pies, were randomly purchased from vendors around the school premises using aseptic techniques. Microbiological analyses of the samples were carried out using culture media, following standard procedures. Identification of the isolates was based on cultural, morphological, and biochemical characteristics. Antibiotic susceptibility pattern of isolates were determined using Kirby Bauer disk diffusion method. Mean percentage occurrences of microbial contaminants in the snacks are Staphylococcus aureus (25.64%), Enterococcus sp. (12.82%), Bacillus sp. (12.82%), Aspergillus sp. (12.82%), Pseudomonas sp. (10.26%), Fusarium sp. (10.26%), Escherichia coli (7.69%), and Penicillium sp. (7.69%). Mean total aerobic plate counts (APC) ranged from 0.8 x 102 - 1.16 x 106 CFU/g. Based on the International Commission for Microbiological Specification for Foods (ICMSF) for APC, the snack samples from ADPS was satisfactory. Lowest percentage of the isolates (48.72%) that demonstrated antibiotic resistance was against ceftazidime, while the highest (71.79%) involved nitrofurantoin. To avert the outbreak of food borne diseases, strict monitoring of hygienic and sanitary practices of snack producers and vendors by the school management and relevant authorities are recommended.